RESPON TANAMAN JAGUNG MANIS (Zea mays L. Saccharata) TERHADAP PEMBERIAN PUPUK KALIUM DAN PUPUK KANDANG KAMBING - Arif, Abdul; Putra, Irwan Agusnu; Nadhira, Ahmad (Jurnal Agroteknologi (Agronu), 2023)
The low quantity and quality of sweet corn is strongly influenced by the low quality of soil and nutrients for which there is no continuous improvement making it difficult for farmers to improve the quality of sweet corn production, so research is carried out on the application of potassium fertilizer and manure to determine the growth and production of sweet corn. This research was conducted in Sei Buluh Village, Teluk Mengkudu District, Serdang Bedagai Regency from February 2022 to May 2022. This study used a Randomized Block Design (RBD) with two factors, Factor 1. KCL fertilizer 3 treatment levels, K0 = control, K1 = 1.40 g/plant. K2 = 2.80 g/plant. and Factor 2. Goat manure 4 treatment levels: P0 = control. P1 = 4 kg/plot. P2 = 8 kg/plot. P3 = 12 kg/plot. Parameters observed were plant height (cm), number of leaves, cob weight and sweetness level. Data were analyzed using Duncan Multiple Range Test (DMRT) at 5% level. The results showed that the K2 treatment of 2.80g/plant of KCL fertilizer was the best treatment for plant height and corn cob weight. The P3 treatment of 12 kg/plot of goat manure was the best treatment for the number of leaves and the weight of corn cobs. K2P3 treatment became the best interaction on the weight parameter of corn cobs with a weight of 197.42. Keywords : Corn, Potassium, Goat Manure